PENGUNGKAPAN PERTANGGUNGJAWABAN KEUANGAN PARTAI POLITIK - Isnani Yuli Andini; Dedy Arfiyanto; M. Munir Syam AR (Fakultas Ekonomi dan Bisnis, 2020)
Political parties are required to make improvements in building transparency and accountability. Developing political ethics in financial management that stands on the values ​​of accountability and transparency. The purpose of this study is to determine the party's financial governance including disclosure of financial accountability. Research results obtained regarding the accountability and financial transparency of the Gerindra party began to apply according to standards. Gerindra party financial management has also begun to be accessed by all parties through the party's official website, so that in 2014 the Gerindra party was named the Public Information Category for Political Parties by the Central Information Commission (KIP) as well as the results of the Indonesia Survey Center (ISC) survey which states that Gerindra is a party which is perceived as clean of corruption cases. With this title the Gerindra Party became the political party that won the third most national votes in the 2019 general election.